Character Values in Palangkahan Tradition In The West Sumatra Community - Zulkarnain Yani; Apria Putra; Irwan Malin Basa (IBDA` : Jurnal Kajian Islam dan Budaya, 2021)
This paper discusses the character values that were taken from the palangkahan tradition. The Palangkahan tradition that exists in West Sumatera society originates from the manuscript or texts obtained from the murshid or tarekat teachers. This tradition is still sustainable and carried out by the community, not only in the islands of West Sumatera, but also in the coastal areas of West Sumatera. Palangkahan tradition is the local wisdom of the people of West Sumatera which has been passed down from generation to generation, which is used before carrying out certain activities in their daily lives. The revealed character values can be used as guidelines for the development of Indonesian people with a strong religious understanding based on local wisdom. The character values contained in this tradition are mushawarah (consultation), discipline, positive thinking, and love of culture.